Stress-induced DNA damage biomarkers: applications and limitations - Nikitaki, Zacharenia; Hellweg, Christine E.; Georgakilas, Alexandros G.; Ravanat, Jean-Luc (Frontiers in Chemistry, 2015)
A variety of environmental stresses like chemicals, UV and ionizing radiation and organism’s endogenous processes like replication stress and metabolism can lead to the generation of reactive oxygen and nitrogen species (ROS/RNS) that can attack cellular vital components like DNA, proteins and lipid membranes. Among them, much attention has been focused on DNA since DNA damages play a role in several biological disorders and aging processes. Thus, DNA damage can be used as a biomarker in a reliable and accurate way to quantify for example radiation exposure and can indicate its possible long term effects and cancer risk. Based on the type of DNA lesions detected one can hypothesize on the most probable mechanisms involved in the formation of these lesions for example in the case of UV and ionizing radiation (e.g. X- or α-, γ-rays, energetic ions, neutrons). In this review we describe the most accepted chemical pathways for DNA damage induction and the different types of DNA lesions, i.e. single, complex DNA lesions etc. that can be used as biomarkers. We critically compare DNA damage detection methods and their limitations. In addition to such DNA damage products, we suggest possible gene inductions that can be used to characterize responses to different types of stresses i.e. radiation, oxidative and replication stress, based on bioinformatic approaches and stringent meta-analysis of literature data.